The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1038/nm.2091
|View full text |Cite
|
Sign up to set email alerts
|

Effective and selective targeting of leukemia cells using a TORC1/2 kinase inhibitor

Abstract: Targeting the mammalian target of rapamycin (mTOR) is a promising strategy for cancer therapy. However, the mTOR kinase functions in two complexes, TORC1 and TORC2, neither of which is fully inhibited by the allosteric inhibitor rapamycin or analogs. We compared rapamycin with the active-site TORC1/2 inhibitor PP242, in acute leukemia models harboring the Philadelphia chromosome (Ph) translocation. We demonstrate that PP242, but not rapamycin, causes death of mouse and human leukemia cells. In vivo, PP242 dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
364
1
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 320 publications
(392 citation statements)
references
References 48 publications
25
364
1
1
Order By: Relevance
“…17,18 However, these drugs, by inhibiting PI3K, could also result in more toxic side effects than rapamycin/rapalogs. 39 At present, the new frontier of mTOR inhibition is represented by the use of active site mTOR inhibitors, which target both mTORC1 and mTORC2, without affecting PI3K activity. 9 Accordingly, in our current study we tested the anti-leukemic activity of three compounds that directly target the mTOR catalytic domain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17,18 However, these drugs, by inhibiting PI3K, could also result in more toxic side effects than rapamycin/rapalogs. 39 At present, the new frontier of mTOR inhibition is represented by the use of active site mTOR inhibitors, which target both mTORC1 and mTORC2, without affecting PI3K activity. 9 Accordingly, in our current study we tested the anti-leukemic activity of three compounds that directly target the mTOR catalytic domain.…”
Section: Discussionmentioning
confidence: 99%
“…9 Accordingly, in our current study we tested the anti-leukemic activity of three compounds that directly target the mTOR catalytic domain. Two of these compounds (PP-242 and OSI-027) have already been tested in other hematological cancers, including Philadelphia þ acute leukemias 39,40 and multiple myeloma, 41 and promising preclinical data were reported.…”
Section: Discussionmentioning
confidence: 99%
“…The mTOR ATP-competitive inhibitors are just beginning to be tested for clinical efficacy, and it is hoped that they will outperform rapamycin in the clinic. In a few preclinical studies, the mTOR catalytic inhibitors were shown to induce cell death in combination with other inhibitors (Janes et al 2010;Sini et al 2010).…”
Section: Mtor and Cell Survivalmentioning
confidence: 99%
“…Also presented in this figure are the sites of action of mTOR inhibitors, some of which have been evaluated in leukemia. 70,71 Akt inhibits tuberous sclerosis 2 (TSC2 or hamartin) function through direct phosphorylation. 72 TSC2 is a GTPase-activating protein that functions in association with the putative TSC1 (or tuberin) to inactivate the small G-protein Rheb.…”
Section: Downstream Targets Of Akt Regulating Mtor Activitymentioning
confidence: 99%